2014
DOI: 10.1177/1545968314521009
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Hemisphere Repetitive Transcranial Magnetic Stimulation for Rehabilitation of Poststroke Aphasia

Abstract: This is the first clinical study of dual-hemisphere rTMS in poststroke aphasia. Combining dual-hemisphere rTMS with language training might be a feasible treatment for nonfluent aphasia; further multicenter studies are needed to confirm this result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 36 publications
2
61
0
1
Order By: Relevance
“…After evaluating the full texts for more details, 12 RCTs satisfied the inclusion criteria. However, after excluding 8 studies (16-23) with duplicate publication (19)(20)(21)(22)(23) and no response to the request for data (16)(17)(18), 4 RCTs (24-27) with a total of 132 patients were included in the analyses. A flow chart of the structured review is shown in Fig.…”
Section: Selected Studies and Characteristicsmentioning
confidence: 99%
“…After evaluating the full texts for more details, 12 RCTs satisfied the inclusion criteria. However, after excluding 8 studies (16-23) with duplicate publication (19)(20)(21)(22)(23) and no response to the request for data (16)(17)(18), 4 RCTs (24-27) with a total of 132 patients were included in the analyses. A flow chart of the structured review is shown in Fig.…”
Section: Selected Studies and Characteristicsmentioning
confidence: 99%
“…Therefore, we believe that a more effective rTMS method is needed for individuals whose right hemisphere is activated during a pre-intervention language localization task. Khedr et al [10] suggested, in their report of dual-hemisphere rTMS on patients with aphasia, that high-frequency rTMS (HFS) to the right hemisphere may be effective for patients with an extensive infarction and left middle cerebral artery occlusion because there may be significant compensation within the right homologous regions of the language area.…”
Section: Introductionmentioning
confidence: 99%
“…NIRS can be used to probe brain function through an intact skull by detecting changes in blood hemoglobin concentrations associated with neural activity. NIRS is one of the alternative noninvasive methods used to observe changes in the cerebral function [10]. In addition, it is used to assess the efficacy of TMS.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, besides the improvements in expressive language, rTMS can improve receptive language performance as well [31]. Some authors reported an association between changes in brain activity induced by rTMS and language improvement [4,33,34], while others did not [12]. Barwood et al [32], Chieffo et al [11] and Seniów et al [5] observed that the patients that obtained larger improvements were those with global aphasia and more severe deficits, suggesting that this tool can modulate language performance even in individuals with quite significant lesions.…”
Section: Tms Interventions In Aphasiamentioning
confidence: 99%